2006
DOI: 10.1007/s00167-006-0070-5
|View full text |Cite
|
Sign up to set email alerts
|

Mobile versus fixed-bearing total knee arthroplasty: mid-term comparative clinical results of 216 prostheses

Abstract: Since the late 1970s, mobile-bearing total knee designs have been advocated as having theoretical advantages over fixed-bearing total knee replacements. At present there is no consensus as to whether there are any differences in clinical results between the two designs. We present the results of two consecutive cohorts each of over 100 prosthesis. The first cohort underwent a fixed-bearing prosthesis, whilst the second cohort received the mobile bearing variant of the same prosthesis. Both groups were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…In one knee with a mobile-bearing prosthesis, the preoperative femorotibial alignment was 11°o f valgus. The preoperative femorotibial alignment averaged 8.9°of varus (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in all knees with a fixed-bearing prosthesis. The postoperative femorotibial alignment Fig.…”
Section: Radiographic Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In one knee with a mobile-bearing prosthesis, the preoperative femorotibial alignment was 11°o f valgus. The preoperative femorotibial alignment averaged 8.9°of varus (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in all knees with a fixed-bearing prosthesis. The postoperative femorotibial alignment Fig.…”
Section: Radiographic Resultsmentioning
confidence: 99%
“…The postoperative femorotibial alignment Fig. 1 Photographs of the mobile-bearing prosthesis in the right and fixed-bearing prosthesis in the left averaged 5.3°of valgus (1)(2)(3)(4)(5)(6)(7)(8) in the mobile-bearing knees and 5.4°of valgus (2)(3)(4)(5)(6)(7)(8) in the fixed-bearing knees. In both groups, there were no significant differences in the position of the femoral and tibial components in the coronal and sagittal planes ( Fig.…”
Section: Radiographic Resultsmentioning
confidence: 99%
“…These include randomised controlled trials [6-8, 15-17, 23], prospective case series [9,10] and retrospective reviews [12][13][14]24]. In these studies a variety of knee replacements have been used, but often prostheses of different design and different manufacturers were compared with each other [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…In these studies a variety of knee replacements have been used, but often prostheses of different design and different manufacturers were compared with each other [6][7][8][9][10]. None of these studies showed a statistically significant difference between the mobile and fixed bearing, but the use of different types and designs of implants may have affected the clinical outcome as has previously been acknowledged by Biau et al [24] and Kim et al [15].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, we included 34 clinical trials with 4754 patients (6861 TKRs) in the meta-analysis. [4][5][6][7][11][12][13][14][15][16][17][18][19] There were 32 RCTs, two were CCTs, 6,29 and two were from the same trial. 23,41 The characteristics of the studies that were included are shown in Tables I and II.…”
Section: Methodsmentioning
confidence: 99%